The Role of Pai Teachers in Overcoming Bullying at SMK Muhammadiyah 1 Genteng Banyuwangi - M. Dani Rahman; Muh. Wasith Achadi (Edumaspul: Jurnal Pendidikan, 2024)
This study aims to analyze the role of Islamic Religious Education Teachers (PAI) in overcoming bullying at SMK Muhammadiyah 1 Genteng Banyuwangi. Bullying is a problem that often occurs in the school environment and can have a negative impact on student development, both psychologically and socially. PAI teachers have an important role in instilling moral and religious values that can prevent and overcome acts of bullying. This study uses a qualitative approach with a descriptive method. Data was collected through interviews, observations, and documentation with informants consisting of PAI teachers, students, and school staff. Data analysis was carried out using the interactive data analysis technique of the Miles and Huberman model, with the validity of the data tested through source triangulation. The results of the study show that the bullying school case at SMK Muhammadiyah 1 Genteng is caused by: students' ignorance of limitations or excessive joking, misunderstandings, shortcomings, lack of education about anti-bullying, negative use of social media, and lack of supervision carried out. In overcoming bullying incidents in the school environment, Islamic religious education teachers at SMK Muhammadiyah 1 Genteng provide guidance and direct students in the teachings of kindness. With various steps and strategies, including: understanding and identifying behavior first, providing activities to develop social skills, providing education about bullying and religious understanding, collaborating with parents and school staff, and enforcing discipline by providing punishment according to school policy